Impacto de la actividad hotelera en el desarrollo sostenible en el cantón Quevedo, año 2021 - Muriel Moran, Aracelly Fernanda (2021)
This research process is based on the broad observation of multiple socioeconomic sectors and the sustainable development of tourism according to the hotel industries. Its purpose is to study and analyze the impacts of sustainable practices in hotel management of greater economic impact of a specific area of the canton to the country, the system for socio-cultural development and commercial sustainability in hotel tourism, is to achieve a business balance that is feasible and ensures organizational sustainability of the same. Tourism is one of the most important factors in economic development in the cultural sphere due to the diversity of favorable activities it acquires in the global economic expansion. The provisioning of the organization gives a competitive advantage to the improvement of the hotel services programs, obtaining a positive impact to the economic and tourist development on all contribution made to the bibliographic review in depth to each sector studied. for such reason it is not acceptable that the behavior and treatment towards the tourist is neat and integral in what refers to the services offered. contributing as a conclusion that the hotel industry is part of the economy and sustainability of cultural management, since its profits benefit the owners, workers and the canton in the socioeconomic sector.